Analysis of Factors Driving Impulsive Buying through Live Streaming Shopping Tiktok Shop - Afina Ghaissani; Anas Hidayat (Economic Education Analysis Journal, 2025)
This study aims to see what factors drive this impulsive buying behavior, especially when purchasing fashion products using TikTok Shop live streaming. This study uses a convenience and non-probability sampling method conducted on 259 respondents. This study's primary data analysis method is the Partial Least Square Structural Equation Model PLS-SEM. Then, the data processing of this study was carried out with the help of IBM SPSS Statistics 24 and SmartPLS 3.0 software. The data is processed application and showed that convenience does not affect perceived enjoyment, but Demand has a significant impact. Furthermore, product usefulness influences perceived usefulness, but product price does not. Then, the perceived enjoyment variable affects perceived usefulness, and both variables positively impact encouraging impulsive buying intention in the TikTok Shop live streaming shopping environment. This research is expected to be useful for companies or fashion businesses that want to promote their products through live-streaming shopping. This research helps them develop strategies to captivate consumer attention and increase sales in the live-streaming shopping environment. Analyzing the driving factors of impulsive buying through TikTok Shop live streaming shopping has significant managerial implications, especially in improving marketing strategies and business management. These implications include a deeper understanding of consumer behavior, increasing the effectiveness of promotions, and developing more relevant products and services.